2017
DOI: 10.1111/bjh.14547
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world use of pomalidomide and dexamethasone in double refractory multiple myeloma suggests benefit in renal impairment and adverse genetics: a multi‐centre UK experience

Abstract: Myeloma patients who become refractory to immunomodulatory agents (IMiDs) and bortezomib have poor survival, with limited therapeutic options. Pomalidomide has shown improved survival and good tolerability in this patient cohort in clinical trials, but real world data are scarce. We retrospectively analysed all patients treated with pomalidomide at five UK centres between 2013 and 2016. Of 85 patients identified, 70 had sufficient information for response assessments. Median age was 66 years [40-89], 96·5% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
2
26
1
2
Order By: Relevance
“…7 In general, results of our study are comparable to other randomized clinical studies including ORR of 39.1% (compared with 31% in MM-003 and 32.6% in MM-010) and real-world studies. 6,7,[11][12][13] We found statistically more effective is treatment with POM/DEX/ BORT but we did not find any differences In conclusion, the real-world Polish cohort of RRMM patients has confirmed that pomalidomide is an active drug in this setting and has demonstrated similar response rates, and OS compared with the phase 3 MM-003, MM-010, and other real-world studies.…”
Section: Discussionmentioning
confidence: 47%
“…7 In general, results of our study are comparable to other randomized clinical studies including ORR of 39.1% (compared with 31% in MM-003 and 32.6% in MM-010) and real-world studies. 6,7,[11][12][13] We found statistically more effective is treatment with POM/DEX/ BORT but we did not find any differences In conclusion, the real-world Polish cohort of RRMM patients has confirmed that pomalidomide is an active drug in this setting and has demonstrated similar response rates, and OS compared with the phase 3 MM-003, MM-010, and other real-world studies.…”
Section: Discussionmentioning
confidence: 47%
“…POM was used at late-stage RRMM. The median patient age (range) was 72 (58-84) years, which was higher compared with that reported in other real-world or large-scale phase 3 trial data 59 (32-78) years in Sriskandarajah et al (12), 61 (41-82) years in Maciocia et al (13) and 66 (37-88) years in the MM-010 trial (9). In the present study, 85.7% of patients were aged >70 years, which was a higher rate compared with the other studies.…”
Section: Discussionmentioning
confidence: 59%
“…However, this analysis showed that patients with moderate RI (defined as CrCl ≥30 to <60 ml/min) had a significantly shorter OS compared to those patients without RI. The discrepancy in OS between the two studies (Siegel et al, 2016;Maciocia et al, 2017) may be due to the small number of patients included in the study by Maciocia et al (2017) not allowing a statistically significant difference to be reached in terms of OS, which, in patients with RI, is half that of those without RI.…”
mentioning
confidence: 96%
“…However, this analysis showed that patients with moderate RI (defined as CrCl ≥30 to <60 ml/min) had a significantly shorter OS compared to those patients without RI. The discrepancy in OS between the two studies (Siegel et al, 2016;Maciocia et al, 2017) may be due to the small number of patients included in the study by Maciocia et al (2017) not allowing a statistically significant difference to be reached in terms of OS, which, in patients with RI, is half that of those without RI.Although RI in MM is not even remotely solved, Maciocia et al (2017) have shown that, in clinical practice, we have further weapons, such as pomalidomide, to treat advance stage MM patients with RI. The MM-013 trial, designed for advanced stage MM patients with moderate, severe and endstage RI, demonstrated that pomalidomide is safe at routine doses in all groups of patients, with a similar response rate (Ramasamy et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation